Increasing the Profitability of Florida Alligator Carcasses - F. W. Leak; T. J. Lane; Dwain D. Johnson; J. W. Lamkey (EDIS)
This document is AN137, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2003.